2023
DOI: 10.1021/acs.jmedchem.3c01370
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress and Prospects of Small Molecules for NLRP3 Inflammasome Inhibition

Na Li,
Ruijia Zhang,
Minghai Tang
et al.

Abstract: NLRP3 inflammasome is a multiprotein complex involved in host immune response�which exerts various biological effects by mediating the maturation and secretion of IL-1β and IL-18�and pyroptosis. However, its aberrant activation could cause amplification of inflammatory effects, thereby triggering a range of ailments, including Alzheimer's disease, Parkinson's disease, rheumatoid arthritis, gout, type 2 diabetes mellitus, and cancer. For the past few years, as an attractive anti-inflammatory target, NLRP3-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Total cell numbers were determined using a hemacytometer and adjusted to 2.6 × 10 6 cells/mL in RPMI GlutaMAX medium containing 1% FBS, 1% penicillin/streptomycin, and 20 mM HEPES, pH 7.3. The LPS/ATP challenge assay was conducted as previously detailed . Briefly, 0.1 mL (2.6 × 10 5 cells) of the PBMC suspension was added to each well of 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total cell numbers were determined using a hemacytometer and adjusted to 2.6 × 10 6 cells/mL in RPMI GlutaMAX medium containing 1% FBS, 1% penicillin/streptomycin, and 20 mM HEPES, pH 7.3. The LPS/ATP challenge assay was conducted as previously detailed . Briefly, 0.1 mL (2.6 × 10 5 cells) of the PBMC suspension was added to each well of 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Heparin-stabilized blood from healthy volunteers was subjected to a 2-step activation protocol as previously described. , Blood samples were diluted with RPMI GlutaMAX medium containing 20 mM HEPES, pH 7.3 (2 parts blood to 1 part medium), after which 0.14 mL of the diluted samples were placed in individual wells of a 96-well plate designated not to receive LPS. To the remaining diluted blood sample, an appropriate volume of 1 μg/mL LPS was added to achieve a final concentration of 100 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IL-1β has been shown to play an important role in chronic diseases such as gout or type 2 diabetes as well as in neuroinflammatory disorders including multiple sclerosis, Alzheimer’s disease, or diabetic neuropathy. Moreover, the CANTOS study, a secondary risk prevention study in cardiovascular disease with the IL-1β monoclonal antibody canakinumab, has shown that IL-1β contributes to cardiovascular risk, lung cancer, and osteoarthritis. NLRP3, as the main inflammasome sensor for sterile danger signals associated with many of these diseases, has become an attractive therapeutic target for low-molecular-weight drug discovery, with the potential to inhibit IL-1β, IL-18, and pyroptosis, and penetrate tissues inaccessible to biologics . The publication of MCC950 (also known as CP-456,773 or CRID3), as a bona fide NLRP3 inhibitor, and the subsequent confirmation of its direct binding to the NLRP3 NACHT domain by biochemical methods and crystallography, have allowed for a first wave of MCC950 -derived NLRP3 inhibitors such as ZYIL1 , GDC-2394 , and NT-0796 (Figure ) to enter early clinical development. These compounds have potential liabilities, including liver toxicity, , so broader chemical diversity is needed to maximize chances of developing a safe and efficacious NLRP3 inhibitor. In this paper, we describe the discovery of tricyclic NLRP3 inhibitors which have been optimized from an initial screening hit to an advanced preclinical candidate.…”
Section: Introductionmentioning
confidence: 99%
“…17 MCC950 is the well-known NLRP3 inhibitor. 18 Recent years, a large number of MCC950 analogs 19 have emerged while given the limited number of inhibitors in clinical trials, thus it is of great significance to develop novel inhibitors of NLRP3. Designing NLRP3 inhibitors is challenging with conventional drug design methods.…”
Section: ■ Introductionmentioning
confidence: 99%